Peningkatan Keterampilan 4C Melalui Model Pembelajaran Berbasis Portofolio - Iwan Fajri; Khairan Ar; Andika Prajana; Yusran Yusran; Sanusi Sanusi (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The researchaaims to describeathe results of the improvement of 4C skills through a portfolio-based citizen project learning model. In addition, this study aims to analyze the hypotheses resulting from the improvement of 4C skills through a portfolio-based project citizen learning model. The research method used in this study is a pre-experimental research design One-Group Pretest-Posttest Design (One group pre-test). The results of the study show that the average value of the 4C skills statistical analysis before being taught with the project citizen learning model is 3.904 then increasing to 4.116 after being taught with the project citizen learning model. The results of hypothesis testing from thisastudy are thatathere is a significant increase in the implementation of a citizen-based project portfolio model for the 4C skills ofastudents. This is indicatedaby the valueaof sig. (2-tailed) is smaller than 0.05 α (0.005 <0.05) basedaon thearesults of the analysis through the SPSS program. Basedaon the resulta of the study it can beaconcluded that learning through the project citizenamodel can improve the 4C skills of students. It is expected that teachers of all subjects can use the project citizen learning model to improve 4C skills with the material in accordance.